2017
DOI: 10.1109/tap.2017.2670616
|View full text |Cite
|
Sign up to set email alerts
|

Equivalent Transmission Line Models for the Analysis of Edge Effects in Finite Connected and Tightly Coupled Arrays

Abstract: Abstract-In this paper we present an analysis of the edge effects in wideband connected arrays of slots and dipoles. Due to the strong mutual coupling between the elements, these arrays can support the propagation of guided waves along their surface. Such waves arise from the edges of the finite array and can be especially detrimental for the performance, since they can travel within the array without geometrical spreading. In this work we introduce Green's function based equivalent transmission line models to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 14 publications
2
18
0
Order By: Relevance
“…The x-oriented slot is assumed to be electrically narrow and excited by a feeding gap, which is small in terms of the wavelength (δ-gap excitation). First, an infinite slot is considered as in [12], where it was shown that the voltage along the slot is represented accurately by:…”
Section: Mom Solution For Semi-infinite Slotmentioning
confidence: 99%
See 3 more Smart Citations
“…The x-oriented slot is assumed to be electrically narrow and excited by a feeding gap, which is small in terms of the wavelength (δ-gap excitation). First, an infinite slot is considered as in [12], where it was shown that the voltage along the slot is represented accurately by:…”
Section: Mom Solution For Semi-infinite Slotmentioning
confidence: 99%
“…However, introducing losses in the ground plane [12], [15] or a thin dielectric substrate, the pole singularity moves away from the branch point in the complex k x -plane, so that the polar contribution can be isolated. The location of the pole, k xp , can be found using a local-search algorithm (e.g.…”
Section: Equivalent Transmission Line Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…In connected arrays, it is especially important to assess the finite edge effects [25], [26]. To demonstrate the effect of the finiteness, we simulate infinite-by-finite arrays using the semi-analytical tool presented in [16].…”
Section: Investigation On the Edge Effectsmentioning
confidence: 99%